ANALISIS GAYA KEPEMIMPINAN JOE BIDEN TERHADAP KEBIJAKAN AMERIKA SERIKAT - Milenia, Ni Putu Wintana; Erawan, I Ketut Putra (Jurnal Nawala Politika, 2023)
This research seeks to explain the leadership style of Joe Biden as President of the United States who was elected in the 2020 American general election. Since Joe Biden's victory, policies in the United States have changed researchers are assisted by Herujito's leadership style perspective. In analyzing qualitative research methods with literature studies that focus on data or findings from books, journals, articles, news, and several other scientific works. The findings in the study sought to examine the personality of Joe Biden. Joe Biden is someone who has an open and brave character in the face of bringing change so that it is included in the collegial leadership style. This has made changes in policies in the United States that are more open in conducting cooperative relations with foreign countries